Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1186/1475-2891-9-54
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory dietary polysaccharides: a systematic review of the literature

Abstract: BackgroundA large body of literature suggests that certain polysaccharides affect immune system function. Much of this literature, however, consists of in vitro studies or studies in which polysaccharides were injected. Their immunologic effects following oral administration is less clear. The purpose of this systematic review was to consolidate and evaluate the available data regarding the specific immunologic effects of dietary polysaccharides.MethodsStudies were identified by conducting PubMed and Google Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
148
0
13

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(166 citation statements)
references
References 145 publications
0
148
0
13
Order By: Relevance
“…Different studies showed that bioactive polysaccharides and extracts could stimulate blood mononuclear cells to increase cytokines, tumor necrosis factor, interferon and interleukins production, induce apoptosis and meaningfully increased the lifespan of the tumor-implanted mice (Paterson, 2006;Ramberg et al, 2010;Roupas et al, 2010;Liao et al, 2013).…”
Section: Ganoderma Polysaccharidic Extracts/fractionsmentioning
confidence: 99%
“…Different studies showed that bioactive polysaccharides and extracts could stimulate blood mononuclear cells to increase cytokines, tumor necrosis factor, interferon and interleukins production, induce apoptosis and meaningfully increased the lifespan of the tumor-implanted mice (Paterson, 2006;Ramberg et al, 2010;Roupas et al, 2010;Liao et al, 2013).…”
Section: Ganoderma Polysaccharidic Extracts/fractionsmentioning
confidence: 99%
“…In addition, glucan manifested significant effects in prevention or modulation of infectious diseases (Renzetti et al, 2009;Ramberg et al, 2010;Novak and Vetvicka, 2008). Some recent observations showed that glucan has palative anti-allergic effects (Ku et al, 2012), even in children with respiratory problems (Jesenak et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…A solid review summarizes immunomodulatory activities of various botanical extracts in both animal and human models (Ramberg et al, 2010). Beta glucans are known for not only reduction of clinical manifestation of respiratory infections, but also for regulation of the psychological state of patients (Talbott and Talbott, 2012).…”
Section: Introductionmentioning
confidence: 99%